2017
DOI: 10.1002/mnfr.201700478
|View full text |Cite
|
Sign up to set email alerts
|

Beetroot and Sodium Nitrate Ameliorate Cardiometabolic Changes in Diet‐Induced Obese Hypertensive Rats

Abstract: The similar functional and molecular responses to beetroot and sodium nitrate indicate that the nitrate content of beetroot reduced inflammation and improved cardiovascular, liver, and metabolic function in rats with metabolic syndrome, rather than betanin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 63 publications
1
14
1
Order By: Relevance
“…50 As nitrate can be metabolized to nitrite and also exert antioxidant effects, it is possible that it causes similar effects as compared to those associated with nitrite therapy in order to reduce MMP-2 activity in hypertension. In fact, it has already been demonstrated that nitrate can revert the increase in MMP-2 expression caused by a high-fat diet, 59 although the mechanism explaining nitrite-induced MMP inhibition is not entirely known. Under inflammatory conditions, MMP-9 expression and activity are down-regulated by S-nitrosothiols in bronchial epithelial cells.…”
Section: Nitrate and Nitrite Reduce Cardiovascular Remodelling In Hmentioning
confidence: 99%
“…50 As nitrate can be metabolized to nitrite and also exert antioxidant effects, it is possible that it causes similar effects as compared to those associated with nitrite therapy in order to reduce MMP-2 activity in hypertension. In fact, it has already been demonstrated that nitrate can revert the increase in MMP-2 expression caused by a high-fat diet, 59 although the mechanism explaining nitrite-induced MMP inhibition is not entirely known. Under inflammatory conditions, MMP-9 expression and activity are down-regulated by S-nitrosothiols in bronchial epithelial cells.…”
Section: Nitrate and Nitrite Reduce Cardiovascular Remodelling In Hmentioning
confidence: 99%
“…Notably, NO donors facilitate glucose transport in skeletal muscles via the stimulation of glucose transporter type 4 abundance: an important regulatory step for glucose uptake in skeletal muscle, heart, and adipose tissue (17–19). Long-term nitrate deficiency is associated with glucose intolerance, hyperglycemia, and an increased risk of atherosclerosis in mice (20), while the supplementation of nitrate-deficient diets with nitrate improves glucose tolerance, insulin resistance, and dyslipidemia in rodent models of hyperglycemia and diet-induced obesity (21, 22). These findings are consistent with the concept that dietary nitrate may be an essential nutrient (20, 23, 24).…”
Section: Introductionmentioning
confidence: 99%
“…nitric oxide synthase (NOS)-independent mechanism, to increase NO production 7,8 . Importantly, this strategy has been shown to have therapeutic cardioprotective effects in other pre-clinical models of cardiomyopathy [9][10][11][12][13][14] . Pertinent to DOX-induced cardiomyopathy, two foundational studies have been conducted exploring the cardioprotective potential of SN co-supplementation.…”
mentioning
confidence: 99%